Geriatric nutritional risk index and mortality from all-cause, cancer, and non-cancer in US cancer survivors: NHANES 2001–2018 - Qiu, Xiuxiu; Wu, Qidong; Zhang, Yiyi; Zhu, Yingjie; Yang, Ming; Tao, Li (Frontiers in Oncology, 2024)
Background: Malnutrition is strongly correlated with worsened treatment outcomes, reducedOur study conclusively demonstrated a robust correlation between GNRI scores and mortality rates among cancer patients, encompassing all-cause mortality as well as specific mortality related to both cancerous and non-cancerous causes. The GNRI may be a valuable prognostic tool for predicting cancer mortality outcomes, offering insights that may inform nutritional management and influence the clinical treatment strategies for cancer survivors.